From cigarettes to symptoms: the association between smoking and depression in the German National Cohort (NAKO) - Völker, Maja; Callies, Carolin M.; Frank, Josef; Foo, Jerome Clifford; Reinhard, Iris; Zillich, Lea; Klinger-König, Johanna; Grabe, Hans Jörgen; Beule, Achim G.; Erhardt-Lehmann, Angelika; Pabst, Alexander; Riedel-Heller, Steffi G.; et al. (BMC public health, 2026)
Although the association between smoking and depression is well-established, the underlying mechanisms and contextual factors remain insufficiently understood. We examined the association between smoking and depression, including detailed dose-response and timing-related relationships, using baseline data from a large population-based cohort, the German National Cohort (NAKO).